The Ideology of Sufficiency of Colonies, Fiscal Colonial Policies and Economic Development in Colonial Nigeria. - Aloko, Sunday Moses Adebayo; Danmaraya, Ibrahim (Corpus Intellectual, 2024)
Economic underperformance in African countries has continued to spark scholarly discourse to identify the root cause of the problem. While some scholars have blamed colonialism, others have argued that differences in colonial experience in relation to different local circumstances were a determining factor. However, the British policy of making colonies pay for their administration through local sources is often mentioned in colonial historiography but rarely explored adequately. Against this backdrop, this paper examines the structure and efficiency of the British policy of colonies supporting themselves and its effects on colonial spending on administration, modern transport and communication systems, education, and health. The qualitative content analysis method of research was adopted for the realization of the research objectives. The study finds out that the policy was the British initiative to achieve a balance in its mission in West Africa without diverting the British taxpayers’ money. Contrary to the dominant perspective which sees nothing positive about the colonial economy, the study contends that despite the exploitative tendencies of the colonial taxation system, it left Africa better than it met it in terms of material development, and laid a foundation for economic development, which post-colonial Nigeria failed to capitalize on.